2006
DOI: 10.1590/s0100-204x2006001200001
|View full text |Cite
|
Sign up to set email alerts
|

Basic density and pulp yield relationship with some chemical parameters in eucalyptus trees

Abstract: -The objective of this work was to evaluate the use of basic density and pulp yield correlations with some chemical parameters, in order to differentiate an homogeneous eucalyptus tree population, in terms of its potential for pulp production or some other technological applications. Basic density and kraft pulp yield were determined for 120 Eucalyptus globulus trees, and the values were plotted as frequency distributions. Homogenized samples from the first and fourth density quartiles and first and fourth yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Our results suggest that the only correlated response expected from selection for increased wood density within E. globulus subraces is a tendency for lignin and S/G to decrease. A negative phenotypic correlation between S/G and wood density was found in E. globulus by da Seca and Domingues (2006) , a result that occurred at the phenotypic, additive genetic, and subrace levels in the present study. No additive genetic relationship was observed between density and extractives, similar to previous studies that also did not find a genetic ( Miranda and Pereira 2002 ; Poke et al 2006 ) or phenotypic ( Ona et al 1998 ) correlation.…”
Section: Discussionsupporting
confidence: 64%
“…Our results suggest that the only correlated response expected from selection for increased wood density within E. globulus subraces is a tendency for lignin and S/G to decrease. A negative phenotypic correlation between S/G and wood density was found in E. globulus by da Seca and Domingues (2006) , a result that occurred at the phenotypic, additive genetic, and subrace levels in the present study. No additive genetic relationship was observed between density and extractives, similar to previous studies that also did not find a genetic ( Miranda and Pereira 2002 ; Poke et al 2006 ) or phenotypic ( Ona et al 1998 ) correlation.…”
Section: Discussionsupporting
confidence: 64%
“…Small variations of pulp yield and basic density can be predicted from some chemical parameters [ 37 ]. Woods with higher pulp yield had very distinctive syringyl/guaiacyl (S/G), syringaldehyde/vanillin (S/V), and total phenols, independent of basic density.…”
Section: Resultsmentioning
confidence: 99%
“…Wood density and pulp yield have been considered fundamental parameters in tree selection programs for pulping, in addition to tree growth (Silva et al, 2009;Borralho et al, 1993), and density is also a determining factor for the type of paper to be produced. Although, many studies have been showing that the density is vital for quality of pulp production (Scanavaca and Garcia, 2004;Trugilho et al, 2005;Santos et al, 2008b;Horáček et al, 2017), many others have been reported no correlation or weak correlation between these two properties (Miranda and Pereira, 2001;Seca and Domingues, 2006;Mokfienski et al, 2008;Silva et al, 2009). In this context, we highlight that the two species we studied have high wood density, E. pellita (0.939 g.cm -3 ) and E. tereticornis (0.800 g.cm -3 ), and a significant difference can be observed between them.…”
Section: Discussionmentioning
confidence: 99%